2013
DOI: 10.1128/aac.01021-12
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Duration for Uncomplicated Staphylococcus aureus Bacteremia To Prevent Relapse: Analysis of a Prospective Observational Cohort Study

Abstract: In multivariate analysis, primary bacteremia was associated with a trend toward increased treatment failure (P ‫؍‬ 0.06). Therefore, in the treatment of uncomplicated SAB, it seems reasonable to consider at least 14 days of antibiotic therapy to prevent relapse, as practice guidelines recommend. Because of its poor prognosis, primary bacteremia, even with a low risk of complication, should not be treated with short-course therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 42 publications
1
73
0
3
Order By: Relevance
“…Similarly, while AHA guidelines suggest at least 14 days of antimicrobial therapy to treat bacteremia after device removal, our respondents favored longer durations (more than 29 days) for occult S. aureus bacteremia. This may reflect shifts in practice based on studies that demonstrated increased risk of relapsed S. aureus bacteremia with shorter treatment times [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while AHA guidelines suggest at least 14 days of antimicrobial therapy to treat bacteremia after device removal, our respondents favored longer durations (more than 29 days) for occult S. aureus bacteremia. This may reflect shifts in practice based on studies that demonstrated increased risk of relapsed S. aureus bacteremia with shorter treatment times [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…antibiotics for uncomplicated SAB is at least 2 weeks. In a recent prospective cohort study of uncomplicated SAB (as defined by IDSA criteria), receipt of antibiotic therapy for Ͻ2 weeks was associated with a relapse rate of 8% (compared to 0% for those treated for at least 2 weeks) (99). This relapse rate is consistent with the 6% rate of late complications (inclusive of relapse and metastatic complications) for intravascular catheter-associated SAB treated for Ͻ2 weeks identified in a 1993 meta-analysis of 11 studies (100).…”
Section: Outcomes and Managementmentioning
confidence: 99%
“…Staphylococcus aureus infections are associated with significant morbidity and mortality. Inappropriate antimicrobial therapy leads to increased healthcare associated costs, prolonged hospital stay and even increased mortality rates [12,13). Current International and United Kingdom guidelines recommend a minimum of 14 days treatment for uncomplicated bacteraemia and longer treatment such as 4-6 weeks in deep seated infections three [9][10][11].…”
Section: Discussionmentioning
confidence: 99%